Spironucleus Infestations (Spironucleosis) in Freshwater Aquarium Fish - Ruth Francis-Floyd; Roy P. E. Yanong (EDIS)
A group of species of single-celled parasites called Spironucleus cause disease in aquacultured and captive fish. Found in cold, temperate, and tropical climates, Spironucleus species can infect a variety of freshwater and marine ornamental and food fish, as well as crustaceans and shellfish. Five species of Spironucleus are currently recognized: S. salmonicida, S. barkhaus, and S. torosa can infest marine organisms, while S. salmonis and S. vortens can infest freshwater ornamental fish. This revised 4-page fact sheet focuses on S. vortens and its effects on ornamental cichlids, explaining which cichlids are susceptible, how to identify S. vortens, and how to confirm, manage, and prevent S. vortens infestations. written by Ruth Francis-Floyd and Roy P. E. Yanong, and published by the Department of Large Animal Clinical Sciences, November 2015. (Photo credit: Roy P. E. Yanong, UF/IFAS Extension Tropical Aquaculture Laboratory)